Religiosity and its impact on Twitter use and viewing of Islamic reality television shows among university students in Malaysia - Tengku Mohd Azzman Shariffadeen, Tengku Siti Aisha; A. Manaf, Aini Maznina (International Islamic University Malaysia, 2018)
Islamic reality shows presents an alternative brand of entertainment for the Malaysian Muslim community. This television genre can also be perceived as an innovative form of da’wah. Through watching these shows, television viewers interested in faith-based content can increase their religious knowledge, educate themselves on the Islamic beliefs and practices, and identify with suitable Muslim role models featured on these shows. Thus, a major focus of this study is to examine use of social media and television viewing related to Islamic reality shows among Malaysian undergraduate students. The uses and gratification approach postulates that individual differences, such as viewer religiosity may influence media selection and use. Therefore, we propose that those who perceive religion more positively would be more interested in da’wah content, and would therefore be more likely to use Twitter to follow accounts related to the show. A cross-sectional survey is carried out among undergraduate students enrolled in introductory Islamic revealed knowledge and human sciences courses from the International Islamic University of Malaysia (N = 321). Among others, findings indicate that religious individuals are more likely to follow the Twitter account of their favorite Islamic reality show. Also, while viewer religiosity initially influenced frequency of viewing Islamic reality shows, those who tweeted frequently about the show is also more likely to view Islamic reality shows frequently. Finally, those who gratified their relaxation needs by following their favorite Islamic reality show personality on Twitter is more likely to view the show frequently. The repercussions of these findings on the role of religiosity and its effects on social media use and television viewing, based on the uses and gratification perspective is discussed in the paper.